Seroprevalence and Trends in Human Immunodeficiency Virus Among Voluntary Non-Remunerated Blood Donors in a Teaching Hospital: Nine-year Retrospective Study - Muhamad Aidil Zahidin; Noor Haslina Mohd Noor; Marini Ramli; Mohd Nazri Hassan; Zefarina Zulkafli; Salfarina Iberahim; Rosnah Bahar; Shafini Mohd Yusoff; Wan Suriana Wan Abdul Rahman; Marne Abdullah (Gazi Medical Journal)
Objective: Human immunodeficiency virus (HIV) infection, which causes acquired immune deficiency syndrome, is a significant public health problem. HIV infection through blood transfusion remains at the top of any other risk exposure because blood carries a much higher level of HIV than other routes of infection. The aim of this study was to describe the seroprevalence of HIV infection from 2010 to 2019 among donors screened at the transfusion medicine unit in Northeastern Malaysia. Methods: A retrospective study was conducted on voluntary blood donors at the Transfusion Medicine Unit, Hospital Universiti Sains Malaysia, from January 2011 to December 2019. Data such as age, gender, marital status, frequency of donations, and serological results were obtained from the computer system of the blood bank and analyzed. Results: A total of 98,874 individuals donated blood and were screened for HIV infections. Only 29 donors were positive for HIV. Therefore, the overall seroprevalence of HIV infection in blood donors was only 0.03% in the nine consecutive years. The trend of HIV infection among our donors decreased initially but increased again from 2014 to 2019. Conclusion: The prevalence in Northeastern Malaysia province was low compared with previous studies conducted in other regions worldwide. The application of standard operating procedures, with updated equipment, and planning for the use of molecular methods are necessary for the blood transfusion service to monitor transfusiontransmitted infections.